Interest in Entrepreneurship : an exploratory study on engineering and technical students in entrepreneurship education and choosing entrepreneurship as a career - Sh. Ahmad, Fauziah; Baharun, Rohaizat (Faculty of Management and Human Resource Development, 2004)
Entrepreneurship is often thought to be a likely subject for business discipline students but not for technical students. Enterprising elements of entrepreneurship such as evaluating opportunity, developing new products, and handling start-ups are part and parcel of most business management curriculum. As for technical discipline students interested in creating their own organization after graduation, they seem to be left in dark although in many cases they are originators of product ideas. In Malaysia, there is a growing concern that technical students do not have sufficient entrepreneurial skills to venture in business particularly running small and medium enterprise (SME) set-ups. There are comments that these students have narrow business perspectives, less flexible to branch in other working areas and foresee themselves as only job seekers and not job creators. This spells the need for universities to introduce entrepreneurship subjects to non-business disciplines. The research project will concentrate on the topic of entrepreneurship education, with specific emphasis on how this education can be promoted and fostered to technical students. To best help students prepare for these new challenges, this research sought to identify an appropriate set of undergraduate courses for introduction of entrepreneurship elements to technical students and to indicate the level of student interest in these courses. Final year technical students from several public higher learning institutions of Malaysia (IPTAs) were chosen as respondents for the survey. The result shows entrepreneurship education should be incorporated into the non-business disciplines. The implication of the results led to an import set of guidelines, which can be used by educators when designing programs to suit different needs and demands of the technical students.